2012
DOI: 10.1177/0954407012454975
|View full text |Cite
|
Sign up to set email alerts
|

A simple and efficient mild air hybrid engine concept and its performance analysis

Abstract: In this paper, a simplified and more effective approach to achieve mild air hybrid operation in an engine with split intake ports is presented and its performance is analysed. The regenerative engine braking is achieved by operating the engine as a compressor during vehicle deceleration through the application of a cam profile switching device to one of the intake valves. Compared to the previous concepts, the new approach simplifies the control and allows more compressed air to be captured during the compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Therefore, it has confirmed that the use of an intake throttle can be an effective means to controlling the engine braking torque in the air hybrid engine operations. This provides the basis of the engine response map of the compressor mode operation comprising engine braking torque values as a function of throttle positions, which has been used for the vehicle driving cycle analysis [10,11]. Table 4 shows an engine response map which summarises the tank pressure and the intake throttle valve opening as functions of the flow rate (g/cycle) of air mass charged for the engine speed range between 1000 and 2000 rpm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it has confirmed that the use of an intake throttle can be an effective means to controlling the engine braking torque in the air hybrid engine operations. This provides the basis of the engine response map of the compressor mode operation comprising engine braking torque values as a function of throttle positions, which has been used for the vehicle driving cycle analysis [10,11]. Table 4 shows an engine response map which summarises the tank pressure and the intake throttle valve opening as functions of the flow rate (g/cycle) of air mass charged for the engine speed range between 1000 and 2000 rpm.…”
Section: Resultsmentioning
confidence: 99%
“…This provides the basis of the engine response map of the compressor mode operation comprising engine braking torque values as a function of throttle positions, which has been used for the vehicle driving cycle analysis. 10,11…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variable valve actuation (VVA) system could be applied to optimise the opening profiles of exhaust valves for maximum scavenging performance. An additional air transfer valve was included for the air-hybrid operation, 38 which could transfer the brake energy into high-pressure compressed air to be stored and then used for stop-start and boost operations. The application of late DI after the closure of scavenge ports and exhaust valves could avoid fuel short-circuiting in BUSDIG engine.…”
Section: Specifications Of the Two-stroke Busdig Enginementioning
confidence: 99%
“…The simulation showed that the pneumatic hybridisation could recover about 10% of total energy under different conditions. Lee et al 2325 studied a cost-effective mild hybrid pneumatic engine concept for buses and commercial vehicles. The simulation showed that the fuel mass consumed during the New European Driving Cycle (NEDC) was 677 g for a standard vehicle and 631.2 g for a hybrid pneumatic vehicle, indicating a fuel saving effect of 6.8%.…”
Section: Introductionmentioning
confidence: 99%